Pemanfaatan Aplikasi Kahoot sebagai Media Pembelajaran PAI di Sekolah Menengah Kejuruan: Studi tentang Integrasi Nilai Religius dalam Interaktivitas Pembelajaran Digital - KURNIAWAN, RIKZA SYAHRIAL; Salimudin; Ananda Salsabiila Irham; Mokhamad Syaifudin (Mu'allim, 2026)
The development of digital technology demands innovation in the learning process, including in Islamic Religious Education (PAI). Amidst the changing paradigm of 21st-century education, the integration of religious values and digital interactivity has become a strategic necessity in shaping students' character. This study aims to analyze the implementation of the Kahoot application as an interactive learning medium in Islamic Religious Education (PAI) at SMK Unitomo, and how its use can integrate religious values in the context of technology-based learning. The research method used is descriptive qualitative research with a case study approach. Data were collected through observations of learning activities, interviews with headmaster, teachers and students, and documentation of learning activities using Kahoot. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of Kahoot can increase student motivation, participation, and understanding of Islamic Religious Education (PAI) materials. Moreover, the digital interactivity created through Kahoot provides a space for teachers to instill religious values such as honesty, responsibility, and cooperation in a fun learning atmosphere. The process of integrating religious values occurs naturally through an educational game mechanism based on healthy competition.